Peran Kebijakan Moneter Terhadap Pertumbuhan Ekonomi Nasional - Wahyu Muh. Syata; Hikmayani Subur (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This research examines the impact of monetary policy on Indonesia's national economic growth through a qualitative approach using the literature study method. The main focus is to analyze the effectiveness of the monetary policy instruments used by Bank Indonesia, namely the benchmark interest rate (BI-7 Day Reverse Repo Rate), open market operations (OMO), and minimum reserve requirements in creating macroeconomic stability. The research results show that monetary policy plays a vital role in influencing national economic growth, but its effectiveness is affected by various external and internal factors. Expectations of economic actors, global macroeconomic conditions, domestic economic structure, and alignment with fiscal policy are determining factors for the success of monetary policy. Research also reveals that the management of the money supply and appropriate interest rates can encourage investment, increase consumption, and create jobs that play a crucial role in sustainable economic growth. To achieve optimal results, Bank Indonesia needs to implement monetary policy with balance and precision, and coordinate with the government's fiscal policy.